2017
DOI: 10.4049/jimmunol.1601757
|View full text |Cite
|
Sign up to set email alerts
|

MLKL Activation Triggers NLRP3-Mediated Processing and Release of IL-1β Independently of Gasdermin-D

Abstract: Necroptosis is a form of programmed cell death defined by activation of the kinase RIPK3 and its downstream effector, the pseudokinase MLKL. Activated MLKL translocates to the cell membrane and disrupts it, leading to loss of cellular ion homeostasis. Here, we use a system in which this event can be specifically triggered by a small-molecule ligand to show that MLKL activation is sufficient to induce the processing and release of bioactive IL-1β. MLKL activation triggers potassium efflux and assembly of the NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(130 citation statements)
references
References 29 publications
3
126
0
1
Order By: Relevance
“…Cell death was analyzed using a 2-color IncuCyte Zoom in-incubator imaging system (Essen Biosciences), as previously described (Gutierrez et al, 2017; Orozco et al, 2014). Briefly, dead cells were detected by measuring uptake of the cell impermeable dye Sytox Green (Life Technologies).…”
Section: Star Methodsmentioning
confidence: 99%
“…Cell death was analyzed using a 2-color IncuCyte Zoom in-incubator imaging system (Essen Biosciences), as previously described (Gutierrez et al, 2017; Orozco et al, 2014). Briefly, dead cells were detected by measuring uptake of the cell impermeable dye Sytox Green (Life Technologies).…”
Section: Star Methodsmentioning
confidence: 99%
“…A link between the NLRP3 inflammasome and the necroptotic cell death pathway has emerged. In response to necroptotic activators, the kinase RIPK3 and the necroptotic effector MLKL are required to activate the NLRP3 inflammasome and induce IL‐1β release . In this case, MLKL oligomerizes on the cell membrane to induce pore formation, resulting in necroptosis and a reduction in the level of intracellular potassium triggering activation of the NLRP3 inflammasome .…”
Section: Canonical Nlrp3 Inflammasomementioning
confidence: 99%
“…In this case, MLKL oligomerizes on the cell membrane to induce pore formation, resulting in necroptosis and a reduction in the level of intracellular potassium triggering activation of the NLRP3 inflammasome . Of particular interest is that MLKL‐dependent secretion of IL‐1β does not rely on the pyroptosis executor gasdermin D, suggesting that IL‐1β might be released through MLKL‐induced pores instead. These studies further accentuate the complex interplay between the NLRP3 inflammasome and nonpyroptotic cell death pathways.…”
Section: Canonical Nlrp3 Inflammasomementioning
confidence: 99%
“…The kinase activity of RIPK1 and RIPK3 is not required for this atypical non-apoptotic caspase-8 activation and in fact, treatment of cells with a RIPK3 kinase inhibitor enhances LPS-induced caspase-8 activation and thus IL-1β processing (101). Furthermore, recent studies have demonstrated an additional link between necroptosis in inflammasome activation, by showing that MLKL activation, which leads to membrane disruption, can activate the NLRP3 inflammasome in a cell-intrinsic manner by altering ion homeostasis (102, 103). This finding implies that induction of necroptosis is linked inextricably to inflammasome assembly, and that caspase-1 activation and processing of IL-1β and IL-18 likely accompany necroptotic cell death when all are present.…”
Section: The Role Of Ripk3 In Inflammationmentioning
confidence: 99%